Low temperature solution synthesis of silicon, germanium and Si–Ge axial heterostructures in nanorod and nanowire form. Issue 45 (18th May 2018) - Flynn, G.; Stokes, K.; Ryan, K. M.
Abstract : Herein, we report the formation of silicon, germanium and more complex Si–Si x Ge1− x and Si–Ge axial 1D heterostructures, at low temperatures in solution. The incorporation of a reducing agent into the reaction is shown to be effective to lower precursor decomposition temperatures. Abstract : Herein, we report the formation of silicon, germanium and more complex Si–Si x Ge1− x and Si–Ge axial 1D heterostructures, at low temperatures in solution. These nanorods/nanowires are grown using phenylated compounds of silicon and germanium as reagents, with precursor decomposition achieved at substantially reduced temperatures (200 °C for single crystal nanostructures and 300 °C for heterostructures), through the addition of a reducing agent. This low energy route for the production of these functional nanostructures as a wet chemical in high yield is attractive to meet the processing needs for next generation photovoltaics, batteries and electronics.